Impact of COVID-19 on ready-mix concrete (RMC) industry in Ahmedabad – A case study. (2022) - Bhatt, Mauli; Patel, Nisarg; Joshi, Tejas M.; Kamplimath, Hemanth; Shah, Darshan
Abstract: India witnessed its first case of coronavirus infection (COVID-19) on January 27, 2020, in Kerala, India. Since then, the infection has spread rapidly across the country and the pandemic outbreak has affected all industries severely including the construction sector. This study aims to understand the effect of the COVID-19 pandemic on the construction sector, particularly the ready-mix concrete (RMC) industry. An attempt was made to investigate the liabilities and the losses incurred by the RMC industry in terms of income and change in the production of concrete during the coronavirus outbreak. A preliminary survey was carried out to create a database of the RMC plants located nearby the study area i.e., Ahmedabad City in the state of Gujarat, and to prepare a questionnaire using google forms. The RMC plants were visited and from the inputs of RMC officials, statistical insights were drawn. The study reveals that during the COVID-19 lockdown period there was almost a 40% loss in concrete production & 60% loss in the income generated by the ready-mix concrete industry. In addition to this, it was also found that the industry had to pay off liabilities like land rent, electricity bills, staff salaries, etc. during the time of the pandemic. This study provides the opportunity for RMC plants to identify the vital elements involved in the operation of the plant which can be affected due to such pandemic and provides guidelines to reduce the effect of any such pandemic on the plant's production & sales by ensuring the stability of all assets involved in its supply chain.